Health promotion and equity: declaration of the International Conference on Health Promotion (PAHO WashingtonUS, 1992)
Presents the Declaration of the International Conference which met to define health promotion for Latin America and to discuss the principles, strategies and commitments aimed at securing health for all the Region's citizens.
DC